PENGEMBANGAN MEDIA PEMBELAJARAN BERBASISI H5P BERMUATAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM MATERI BARISAN DAN DERET ARITMATIKA PADA SISWA SMA - Dinda; Darma , Yudi; Firdaus , Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to produce learning media in the form of interactive H5P-based learning videos with a problem-based learning model that meets the criteria of validity, practicality, and effectiveness in improving mathematical problem-solving abilities on the topic of arithmetic sequences and series for grade X students at SMA Negeri 1 Jongkong. The method used in this research is Research and Development (R&D) with the Borg and Gall development model ((1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Trial, (7) Product Revision)). The subjects in this research consist of grade X students with a total of 26 students. The instruments used in this research include expert validation sheets, teacher response questionnaires, student response questionnaires, and posttests. The research results show that the developed learning media obtained an average validity percentage of 88.33% with very valid criteria. The practicality of the media based on teacher and student response questionnaires reached an average percentage of 82.84% with very practical criteria. Meanwhile, the posttest results show that the classical completeness of students reached 84%, which falls into the very effective category. Thus, the development of H5P-based learning media with problem-based learning content is feasible and effective for use in mathematics learning to improve students' problem-solving abilities. Keywords: H5P, Problem Based Learning, Problem Solving, Arithmetic Sequences and Series.